Monday

March 2, 2015

March 2, 2015

Posted by **Alex** on Saturday, February 21, 2009 at 6:39pm.

lim(x-->0) (1-cosx)/2x^2

I multiplied the numerator and denominator by (1+cosx) to get

lim(x->0) (1-cos^2x)/2x^2(1+cosx)

= lim(x->0)sin^2x/2x^2(1+cosx)

the lim(x->0) (sinx/x)^2 would =1

I then substituted the remaining portion with 0 and got 1/4

Is this answer right??

- Calculus..more help! -
**bobpursley**, Saturday, February 21, 2009 at 8:04pmOne of the ways to check these is to look a graph of it. Yes, it is right.

**Answer this Question**

**Related Questions**

Calculus - Find the following limits algebraically or explain why they don’t ...

maths - 1)lim [(x+y)sec(x+y)-xsecx]/ y x-o 2)show that lim |x-4|/x-4 does not ...

calculus - using L'Hospital's rule, evalutate; LIM as x->0 e^x +cos x / e^x...

CALCULUS - Could someone please solve these four problems with explanations? I'd...

Calculus - How do I solve lim(x-->pi/4)(sinx-cosx)/cos(2x) The (x-->pi/4) ...

calc - need to find: lim as x -> 0 of 4(e^2x - 1) / (e^x -1) Try splitting ...

Calc II - For the following question, we need to find the length of the polar ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Math - Evaluate the limits lim x^3 + 3/ x->¤ 2x^3 + 4x + 1 lim 1 - cosx / x-&...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...